The Effect of Nahwu Learning Understanding for The Insya - Muhammad Husni Shidqi; Adam Mudinillah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
So far, the success of learning insya' can be seen from the results of student essays when composing Arabic according to good and correct grammar. However, no single study has examined the effect or contribution of understanding Arabic grammar on learning outcomes insya'. Therefore, this study investigates the impact of understanding grammar, especially nahwu, on learning outcomes insya' for students majoring in Arabic language education at the Batusangkar State Islamic Institute. This research uses an experimental approach with the type of Expo Facto. This study indicates that understanding Arabic grammar (Nahwu) does not have a positive impact on the Insya' learning of students in the Arabic language learning department at the Batusangkar State Islamic Institute.